2021
DOI: 10.1371/journal.pone.0246971
|View full text |Cite
|
Sign up to set email alerts
|

High efficient de novo root-to-shoot organogenesis in Citrus jambhiri Lush.: Gene expression, genetic stability and virus indexing

Abstract: A protocol for high-frequency direct organogenesis from root explants of Kachai lemon (Citrus jambhiri Lush.) was developed. Full-length roots (~3 cm) were isolated from the in vitro grown seedlings and cultured on Murashige and Skoog basal medium supplemented with Nitsch vitamin (MSN) with different concentrations of cytokinin [6-benzylaminopurine, (BAP)] and gibberellic acid (GA3). The frequency of multiple shoot proliferation was very high, with an average of 34.3 shoots per root explant when inoculated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Kousalya & Narmatha Bai (2016) 42 found that applying GA3 and BAP combination in a ratio of 1:1 increases shoot elongation but also shoot multiplication of Canscora decussate. This was also supported by in vitro cultures of Citrus jambhiri explants which had a high frequency of multiple shoot proliferation after growing in the presence of GA3/ BAP ratio was 1:1 in the culture media 43 . Nevertheless, in many works on the in vitro culture of the Lavender species, the most effective method for shoot propagation was MS media supplemented with BA hormone alone 33,,44,45 .…”
Section: Discussionmentioning
confidence: 63%
“…Kousalya & Narmatha Bai (2016) 42 found that applying GA3 and BAP combination in a ratio of 1:1 increases shoot elongation but also shoot multiplication of Canscora decussate. This was also supported by in vitro cultures of Citrus jambhiri explants which had a high frequency of multiple shoot proliferation after growing in the presence of GA3/ BAP ratio was 1:1 in the culture media 43 . Nevertheless, in many works on the in vitro culture of the Lavender species, the most effective method for shoot propagation was MS media supplemented with BA hormone alone 33,,44,45 .…”
Section: Discussionmentioning
confidence: 63%
“…They can be easily developed into shoots that ensure clonal fidelity [ 33 ]. Genetic fidelity and true-to-type regenerated plants are very important for both the germplasm maintenance for plant conservation purposes and mass shoot propagation that ensures a continuous supply of uniform genetic plant material for large-scale secondary metabolite production [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ISSR markers did not reveal any variation in the established emblings, thus confirming genetic stability with the current protocol. In citrus, earlier studies also suggest the efficiency of ISSR markers in assessing genetic stability ( Siragusa et al., 2007 ; Meziane et al., 2017 ; Devi et al., 2021 ). The current study is the first report on the genetic stability of in ovulo culture-induced plants obtained through DSE in Kinnow mandarin.…”
Section: Discussionmentioning
confidence: 98%